2013
DOI: 10.1007/s40268-013-0006-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Azelnidipine Tablets on Morning Hypertension

Abstract: BackgroundMorning hypertension is a risk factor for cardiovascular and cerebrovascular events. Furthermore, it is a useful measure for definitive diagnosis of hypertension, and patients who self-assess their own blood pressure (BP) in the morning tend to exhibit better compliance with antihypertensive medication than those who do not.ObjectiveThe objective of this analysis was to determine the BP- and pulse rate-lowering effects of azelnidipine, a long-acting dihydropyridine calcium antagonist administered onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…The At-HOME study [12] was conducted according to Article 14-4 (re-examination) of the Pharmaceutical Affairs Act, Japan, and in compliance with Good Post-marketing Study Practice (GPSP). For a list of participating medical centers [in Japanese], see the electronic supplementary material.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The At-HOME study [12] was conducted according to Article 14-4 (re-examination) of the Pharmaceutical Affairs Act, Japan, and in compliance with Good Post-marketing Study Practice (GPSP). For a list of participating medical centers [in Japanese], see the electronic supplementary material.…”
Section: Methodsmentioning
confidence: 99%
“…From among the patients who were included in the primary analysis of the At-HOME Study [12], cases with evening home BP measurements within 28 days prior to the baseline date are described in this article.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, azelnidipine also significantly decreased plasma Hs-CRP ( P <0.05) concentration and increased 6-keto-PGF1α level to inhibit the formation and development of atherosclerosis. In addition, some previous literature has reported that azelnidipine featured reno-protective, improving insulin resistance, and cerebro-protective effects 16. However there is no relevant research in Chinese.…”
Section: Efficacy Studies Of Azelnidipine In Chinese Patientsmentioning
confidence: 99%